Articulation Work: Insights into examiners’ expertise from their remote feedback interactions - Johnson, Martin (Communication & Language at Work, 2015)
This study reports an exploratory reanalysis of data that was collected as part of an earlier project that focused on the remote feedback messages that passed between professional examiners working within an English awarding body[1]. The examiners in this study are contracted by the awarding body to assess the examination performances of students at the end of a two-year course of study that is a precursor to entry to academic courses in UK Universities. This paper takes its title from a play on the word ‘articulate’, which simultaneously references the notion of ‘expressing’ and Schmidt’s (2011) concept of articulation as the coordination of interconnected work across individuals. In this way, the paper explores evidence that senior examiner feedback to other examiners embodies both codified and tacit elements of expert examiner work. This project, involving 59 examiners from six post-compulsory education subject areas, uses observation, survey and interview methods to gather information about the characteristics of senior examiner feedback. Focusing specifically on senior examiners who generate feedback, analyses suggest that these feedback interactions give insights into overt and hidden functions of examiner work. As a consequence, the analyses carry implications for the on-going development of the examiner community and the development of expertise. [1] In England, Wales and Northern Ireland educational qualifications are offered by awarding bodies that are recognised by the national body that regulates qualifications and examinations (the Office of Qualifications and Examinations Regulation [Ofqual]).